2022
DOI: 10.3390/cancers14051177
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects on the Translation of Immune-Related Alternatively Polyadenylated mRNAs in Melanoma and T Cells by eIF4A Inhibition

Abstract: Targeting the translation initiation complex eIF4F, which binds the 5′ cap of mRNAs, is a promising anti-cancer approach. Silvestrol, a small molecule inhibitor of eIF4A, the RNA helicase component of eIF4F, inhibits the translation of the mRNA encoding the signal transducer and activator of transcription 1 (STAT1) transcription factor, which, in turn, reduces the transcription of the gene encoding one of the major immune checkpoint proteins, i.e., programmed death ligand-1 (PD-L1) in melanoma cells. A large p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
(74 reference statements)
1
2
0
Order By: Relevance
“…Zotatifin reduced the expression of CD154 (CD40L), the interaction partner of CD40 expressed on antigen-presenting cells, whereas CR-31-B (−) and silvestrol did not affect CD154 expression. This is in line with the published data, as Biswas et al also found that silvestrol did not regulate CD154 at the mRNA level in activated T cells [ 32 ]. Moreover, the pharmacological inhibition of elF4A reduced cytokine release (IL10, IFNγ and IL17A).…”
Section: Discussionsupporting
confidence: 92%
“…Zotatifin reduced the expression of CD154 (CD40L), the interaction partner of CD40 expressed on antigen-presenting cells, whereas CR-31-B (−) and silvestrol did not affect CD154 expression. This is in line with the published data, as Biswas et al also found that silvestrol did not regulate CD154 at the mRNA level in activated T cells [ 32 ]. Moreover, the pharmacological inhibition of elF4A reduced cytokine release (IL10, IFNγ and IL17A).…”
Section: Discussionsupporting
confidence: 92%
“…Sema4D is associated with the etiology of various types of cancer. 88,89 Roles for Sema4D have been demonstrated in breast cancer, [90][91][92][93][94][95][96][97][98][99][100][101] colorectal carcer, [102][103][104][105][106][107][108] gastric cancer, 109 esophageal cancer, 110,111 lung cancer, [112][113][114] pancreatic cancer, 107,[115][116][117] cholangiocarcinoma, 118 prostatic cancer, [119][120][121][122][123] bladder cancer, 124,125 kidney cancer, 125 cervical cancer, 126 ovarian cancer, [127][128][129][130] malignant melanoma, 131 osteosarcoma, 132 head-and-neck cancer,…”
Section: Sema4d In Cancermentioning
confidence: 99%
“…Sema4D is associated with the etiology of various types of cancer 88,89 . Roles for Sema4D have been demonstrated in breast cancer, 90–101 colorectal carcer, 102–108 gastric cancer, 109 esophageal cancer, 110,111 lung cancer, 112–114 pancreatic cancer, 107,115–117 cholangiocarcinoma, 118 prostatic cancer, 119–123 bladder cancer, 124,125 kidney cancer, 125 cervical cancer, 126 ovarian cancer, 127–130 malignant melanoma, 131 osteosarcoma, 132 head‐and‐neck cancer, 133–137 medulloblastoma, 138 leukemia, 139–143 malignant lymphoma, 144 and multiple myeloma (Figure 4). 145 Cancer cells express Sema4D or its receptor, which are typically up‐ or down‐regulated in tumors compared to normal tissues.…”
Section: Semaphorins In Pathogenesismentioning
confidence: 99%